2008
DOI: 10.1016/j.vaccine.2008.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of M segment DNA vaccines to Hantaan virus and Puumala virus reduces their immunogenicity in hamsters

Abstract: Connie, "Mixing of M segment DNA vaccines to Hantaan virus and Puumala virus reduces their immunogenicity in hamsters" (2008 b s t r a c tTo determine if DNA vaccines for two hantaviruses causing hemorrhagic fever with renal syndrome, Hantaan virus and Puumala virus, are immunogenic when given in combination, we delivered them to hamsters separately or as mixtures by gene gun or by electroporation. Both vaccines elicited neutralizing antibodies when given alone but when they were delivered as a mixture, antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…The results of studies performed in our laboratory and by others have demonstrated that i.m. EP is a highly effective method for facilitating the uptake and expression of DNA vaccines in multiple animal species (27)(28)(29)44). In addition, i.m.…”
Section: Resultsmentioning
confidence: 99%
“…The results of studies performed in our laboratory and by others have demonstrated that i.m. EP is a highly effective method for facilitating the uptake and expression of DNA vaccines in multiple animal species (27)(28)(29)44). In addition, i.m.…”
Section: Resultsmentioning
confidence: 99%
“…This would reduce the burden of developing specific vaccines for the myriad different pathogenic hantaviruses around the world. Combinations of plasmids co-delivered separately or delivered as mixtures shows promise in animal models [15,32]. Data from these studies have demonstrated that DNA vaccines can also elicit cross-protection against other species of hantaviruses [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…[172]). Apart from that, only two molecular vaccines against HFRS have been tested in humans, the first was recombinant vaccinia-vectored vaccine expressing the M segment of HTNV [173] and the second plasmid DNA [174]. The advantage of DNA vaccines is that they offer an easy way to construct multivalent vaccines and they are able to induce long-lasting humoral and cellular immunity.…”
Section: Preventionmentioning
confidence: 99%